Trade in the Mashreq : An Empirical Examination - Blavy, Rodolphe (Washington, D.C. : International Monetary Fund, 2001)
This paper provides a framework for understanding trade patterns in the Mashreq. An augmented gravity model is used to compare actual with expected levels of trade. Trade barriers, political uncertainty, and over-appreciation of domestic currencies seem to explain low levels of international trade. At the intra-regional level, specific trade barriers between Israel and other Mashreq countries reduce further levels of trade. Quite surprisingly, removing Israel from the sample leads to higher actual intra-regional trade than predicted. The analysis suggests that trade liberalization, correction of currency misalignments, reduction of political uncertainty, and improved trade relations with Israel would boost trade in the region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet